2020
DOI: 10.1111/bph.15003
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol improves survival and behavioural co‐morbidities of Dravet syndrome in mice

Abstract: Background and Purpose: Dravet syndrome is a severe, genetic form of paediatric epilepsy associated with premature mortality and co-morbidities such as anxiety, depression, autism, motor dysfunction and memory deficits. Cannabidiol is an approved anticonvulsive drug in the United States and Europe for seizures associated with Dravet syndrome in patients 2 years of age and older. We investigated its potential to prevent premature mortality and improve associated co-morbidities. Experimental Approach:The efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 69 publications
4
36
0
1
Order By: Relevance
“…However, another phytocannabinoid, CBG, was shown to share blockade of VGSCs but, unlike CBD, had no clear effect on PTZ‐induced seizures in rats (Hill et al, 2014). CBD has also been shown to retain anti‐seizure effects and improve social deficits and survival in a mouse model of DS (Kaplan, Stella, Catterall, & Westenbroek, 2017; Patra et al, 2020), itself a syndrome associated with a loss‐of‐function mutation to Na V 1.1 VGSCs. Moreover, nanomolar CBD was effective in regulating neuronal excitability without effects on VGSCs in a human‐induced pluripotent stem cell‐based model of DS (Sun & Dolmetsch, 2018).…”
Section: Cbd Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another phytocannabinoid, CBG, was shown to share blockade of VGSCs but, unlike CBD, had no clear effect on PTZ‐induced seizures in rats (Hill et al, 2014). CBD has also been shown to retain anti‐seizure effects and improve social deficits and survival in a mouse model of DS (Kaplan, Stella, Catterall, & Westenbroek, 2017; Patra et al, 2020), itself a syndrome associated with a loss‐of‐function mutation to Na V 1.1 VGSCs. Moreover, nanomolar CBD was effective in regulating neuronal excitability without effects on VGSCs in a human‐induced pluripotent stem cell‐based model of DS (Sun & Dolmetsch, 2018).…”
Section: Cbd Mechanism Of Actionmentioning
confidence: 99%
“…In particular, we investigated models of Dravet syndrome (DS), a genetic disease due to a voltage‐gated sodium channel (VGSC) SCN1A gene mutation. It was shown that chronic CBD (100 mg·kg −1 injected subcutaneously twice daily) treatment was able to increase survival in Scn1a −/− mice and prevent premature mortality and improve associated co‐morbidities in Scn1a +/− mice (Patra et al, 2020). Such preclinical work provided a strong association with the clinical data that had emerged following our initial work.…”
Section: Initial Interest In Cannabis Components For Treatment Of Epimentioning
confidence: 99%
“… Zamberletti et al (2019a) found that chronic CBDV administration (at 20 mg/kg/day and others) in Mecp2 knockout mice (a Rett syndrome-like animal model) rescued the impaired short-term recognition memory which was evaluated during adolescence and early adulthood. In addition to CBDV benefits, chronic CBD administration (100 mg/kg twice daily, i.e., 200 mg/kg/day from the neonatal period up to early adulthood) rescued several autistic-like behaviors (anxiety- and depression-like behavior, poor social interaction, and increased rearing behavior, as well as reference memory and working memory) in Scn1a +/− mice, a Dravet syndrome-like animal model ( Patra et al, 2020 ). Importantly, CBD did not induce any adverse effects on motor function, giving further support for the benefits and safety of using these cannabinoids in treating ASD.…”
Section: Reviewed Studies On Autism Spectrum Disordermentioning
confidence: 99%
“…Similarly, the ECB system (that plays an important role in the modulation of several signaling systems) has also been implicated in the pathophysiology of ASD and has become a target for the development of pharmacological therapies ( Wei et al, 2016 ; Zamberletti et al, 2017 ; Pietropaolo et al, 2020 ). Preclinical evidence suggests that its modulation impacts socioemotional reactivity ( Servadio et al, 2016 ; Wei et al, 2016 ; Folkes et al, 2020 ), stereotyped behaviors ( Servadio et al, 2016 ; Melancia et al, 2018 ), learning and memory ( Griebel et al, 2015 ; Qin et al, 2015 ; Melancia et al, 2018 ), susceptibility to seizures ( Kaplan et al, 2017 ; Patra et al, 2019 ; Patra et al, 2020 ), and regulation of circadian rhythm ( Atkinson et al, 2010 ; Vaughn et al, 2010 ). All of them are directly or indirectly related to ASD (for detailed review, see Zamberletti et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, CBD presents different physiological and pharmacological mechanisms of action associated with its anticonvulsant effects and improvement of epilepsy-related neuropsychiatric comorbidities in basic and clinical research (Bergamaschi et al, 2011 ; Devinsky et al, 2014 ; Campos et al, 2017 ; Patra et al, 2020 ). Anxiety- and depressive-like behaviors are associated with genetic predisposition to seizure in strains like WAR, GEPR, KM, and audiogenic-susceptible WAG/Rij rats (Sarkisova and Kulikov, 2006 ; Castro et al, 2017 ; Sarkisova et al, 2017 ; Aguilar et al, 2018 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%